Lokalitas Kitab Tafsir Qoeran Djawen - Zainab Zainab (IAT dan ILHA, UIN KH ABDURRAHMAN WAHID, 2021)
The process of interpreting the Qur'an is not only limited to the practice of understanding a text by a mufasir. More than that, a mufasir engages in a dialogue with existing traditions, culture and socio-politics. Likewise, studying interpretation in Indonesia, especially Java, also concerns the socio-political conditions of the writer, the audience space when the interpretation is written, the language used and the purpose of writing the interpretation are some important studies to be explored. In Java, there are quite a number of interpreters with the characters of their respective interpretations, one of which is the Tafsir Qoeran Djawen book. In this interpretation, it accommodates various local aspects such as script, narrative and communication in the practice of interpretation. Departing from this, the author raises the title